Method on sediment management for restoring the lower reach of the Kelani River, Sri Lanka - Dissanayaka Mudiyanselage Pavithra Sudeshika; Yoshiyuki Imamura; Daisuke Harada; Shinji Egashira (River, 2025)
Abstract The present study describes a river channel management method for restoring riverine environments degraded by sand mining in rivers. Specifically, three conditions that must be met for a restored river channel in the lower reach of the Kelani River in Sri Lanka were proposed: (1) flood discharge capacity of the channel for a given flood, (2) prevention of saltwater intrusion, and (3) creation of a diverse physical environment. The allowable mining volume satisfies the three conditions, while continuing to mine sand was discussed based on the sediment budget calculations in the target river reach. In this case, the amount of sediment stored in the target reach and its variation are determined by the amount of sediment supplied to the target reach, the amount of sediment discharged from the target reach to the sea, and the amount of sediment excavated. This means that the dynamic equilibrium channel of the target reach is determined by the amount of sediment supplied and the amount of sediment excavated. The amount of sand mined when the dynamic equilibrium channel meets the three conditions of the restored channel is a candidate for the allowable amount of sand mined. One of these, the most desirable one, is set as the allowable mining volume. As described above, we proposed a method to develop a restoring reach taking the sediment budget and associated hydraulic and hydro morphological conditions in the target reach into consideration.